The R+0! approach: between theory and practice - Carabelli, Romeo (AESOP, 2014)
Urban development is always related to social transformation. This can be seen in several examples through history, from the French “luxury polemic” of the 18th century, discussing where new real estate should be developed, through the Grossstadt discussion at the beginning of the 20th century about the relevance of the masses, up to the 1968 social protests, when the theory of Lefebvre about the “right to the city”, gave a new interest to the quality of everyday life (Secchi 2013:7). In the last of these, there is an implicit new role for ‘the ordinary citizen’, who became an important stakeholder in the development and regeneration of urban regions. During the seventies several attempts to strengthen the role of citizens in urban planning and design developments were attempted, notably the ones by Yona Friedman and Giancarlo de Carlo, but they did not reach a wide audience, and tended to be only limited, single experiences (Cimadomo, 2014a). They did, however, show the necessity to get the citizen’s opinion and get to know their needs, as a relevant social act in any design and urban transformation intervention, considering not the administration, but the citizens themselves as the real clients. The weight of the real estate and subprime lending components in the financial crisis at the beginning of this century had, and still has, a great impact on the lives of millions of people. In particular, cuts in welfare benefits have generated protests everywhere, giving a renewed importance to the role of citizens in policy-making. The 15M movement in Spain, or Occupy Wall Street in the United States, just to mention two, constitute a profound transformation and a point of no return in the way public policies are administered. Such movements have also had an effect on urban transformation, leading to a more bottom-up approach to, and the participation of, ordinary citizens in the planning process.
Sustainability in heritage protected areas : Book of Proceedings of the 5th AESOP European Urban Summer School Tours, France, from 1st – 8th September 2014